Contribution from different current systems to SYM and ASY midlatitude indices. Issue 9 (15th September 2014) - Dubyagin, S.; Ganushkina, N.; Kubyshkina, M.; Liemohn, M.
Abstract Using empirical magnetospheric models, we study the relative contribution from different current systems to the SYM and ASY midlatitude indices. It was found that the models can reproduce ground‐based midlatitude indices with correlation coefficients between the model and real indices being ∼0.8–0.9 for SYM‐H and ∼0.6–0.8 and ∼0.5–0.7 for ASY‐H and ASY‐D, respectively. The good agreement between the indices computed using magnetospheric models and real ones indicates that purely ionospheric current systems, on average, give modest contribution to these indices. The superposed epoch analysis of the indices computed using the models shows that, nominally, the cross‐tail current gives the dominant contribution to SYM‐H index during the main phase. However, it should be remembered that the model region 2, partial ring current, and cross‐tail current systems are not spatially demarcated (the systems are overlapped in the vicinity of geostationary orbit). For this reason, this result should be taken with a precaution. The relative contribution from symmetric ring current to SYM‐H starts to increase a bit prior or just after SYM‐H minimum and attains its maximum during recovery phase. The ASY‐H and ASY‐D indices are controlled by interplay between three current systems which close via the ionosphere. The region 1 FAC gives the largest contribution to ASY‐H and ASY‐D indices during the main phase, though, region 2 FAC and partial ring current contributions are also prominent. In addition, we discuss the application of these results to resolving the long‐debated inconsistencies of the substorm‐controlled geomagnetic storm scenario.